Pendidikan Jiwa dalam Perspektif Syaikh Ibnu Qayyim al-Jauziyyah - Arsyad Shodiq Shodiq; Siti Rokhimah (Lembaga Yasin AlSys, 2026)
Although the concept of soul education (tarbiyah al-nafs) has received attention in Islamic education studies, research that specifically discusses its comprehensive framework within the classical Islamic scholarly tradition remains limited. This study aims to analyze the concept of soul education according to Syaikh Ibnu Qayyim al-Jauziyyah, including its meaning, methods, and outcomes. This study used a descriptive qualitative approach through library research by examining Ibnu Qayyim’s major works, such as Ar-Ruh, Al-Miftah, Ighathat al-Lahfan, and Tuhfat al-Mawdud. The results show that Ibnu Qayyim’s concept of soul education is holistic, integrating eight main dimensions, namely faith education, spiritual education, intellectual education, emotional education, moral or character education, social education, will or irādah, and physical education. The main methods offered include muhasabah al-nafs or self-introspection, riyadhah al-nufus or spiritual discipline, and dhikrullah. The conclusion of this study affirms that Ibnu Qayyim’s framework of soul education is a relevant and applicable model for addressing the moral and spiritual crisis in the modern era. These findings contribute to the development of classical Islamic education studies and imply the importance of integrating the concept of soul education into contemporary Islamic educational institutions.